2018
DOI: 10.1017/cem.2018.384
|View full text |Cite
|
Sign up to set email alerts
|

Association between ondansetron use and symptom persistence in children with concussions: A 5P substudy

Abstract: CLINICIAN'S CAPSULE What is known about the topic? Most children who sustain a concussion suffer from post-concussion symptoms for many weeks following the accident. What did this study ask? Is there an association between ondansetron administration and the presence of persistent post-concussion symptoms at 1 week and 1 month in children? What did this study find? This observational study found that the use of ondansetron among children presenting to the emergency department with an acute concussion was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A total of 45 healthy participants without mild TBI were included in the control groups of 2 studies . Eight studies examined pediatric participants, totaling 2139 participants with mild TBI who were 18 years or younger . Data extraction summaries are reported in Table 1, and Table 2; meta-statistics are summarized in Figure 1 and Figure 2 and eFigure 2 and eFigure 3 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 healthy participants without mild TBI were included in the control groups of 2 studies . Eight studies examined pediatric participants, totaling 2139 participants with mild TBI who were 18 years or younger . Data extraction summaries are reported in Table 1, and Table 2; meta-statistics are summarized in Figure 1 and Figure 2 and eFigure 2 and eFigure 3 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…This study did not report any substantial benefits associated with ondansetron treatment with regard to postconcussion symptoms, length of hospital stay, or measures assessing the timing of the children’s return to school or normal activity compared with placebo. Gravel et al (moderate risk of bias) also performed a 2019 prospective observational study of 1805 children who received ondansetron treatment less than 24 hours after experiencing a mild TBI event. This study reported that ondansetron therapy was associated with worsening persistent postconcussion symptoms at 1 month after intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation